Study on the long life cycle fuel management of a fast breeder stationary wave reactor - López Solís, Roberto Carlos (My University, 2015)
KANEXT, TWR, Breed/Burn Nuclear Reactor, Reactor Nuclear de Cría/Quemado, Deterministic Code, Código Determinístico, Uranium Cycle, Ciclo del Uranio.
Keywords: KANEXT, TWR, Breed/Burn Nuclear Reactor, Reactor Nuclear de Cría/Quemado, Deterministic Code, Código Determinístico, Uranium Cycle, Ciclo del Uranio.